2007
DOI: 10.1074/jbc.m701996200
|View full text |Cite
|
Sign up to set email alerts
|

TrkA Receptor “Hot Spots” for Binding of NT-3 as a Heterologous Ligand

Abstract: Neurotrophins signal via Trk tyrosine kinase receptors. Nerve growth factor (NGF) is the cognate ligand for TrkA, the brainderived neurotrophic factor for TrkB, and NT-3 for TrkC. NT-3 also binds TrkA as a lower affinity heterologous ligand. Because neurotrophin-3 (NT-3) interactions with TrkA are biologically relevant, we aimed to define the TrkA "hot spot" functional docking sites of NT-3. The Trk extracellular domain consists of two cysteine-rich subdomains (D1 and D3), flanking a leucinerich subdomain (D2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
(53 reference statements)
4
35
0
1
Order By: Relevance
“…3a) or from cisplatin toxicity (data not shown), although this neurotrophin be a TrkA agonist [14, 36]. These data indicate that TrkA agonism by NT-3 and NGF also differ with respect to protection of cytotoxicity; consistent with reports that these ligands differ in terms of their TrkA binding affinity and activation of signaling pathways [13, 14]. …”
Section: Resultssupporting
confidence: 84%
“…3a) or from cisplatin toxicity (data not shown), although this neurotrophin be a TrkA agonist [14, 36]. These data indicate that TrkA agonism by NT-3 and NGF also differ with respect to protection of cytotoxicity; consistent with reports that these ligands differ in terms of their TrkA binding affinity and activation of signaling pathways [13, 14]. …”
Section: Resultssupporting
confidence: 84%
“…We found that there is a third agonistic receptor hot spot on TrkA that is cryptic and silent; but becomes functional when p75 is co-expressed [36]. We also found that the receptor hot spots that TrkA has for binding and function of the heterologous ligand NT-3 are different than those used for NGF binding and function [37].…”
Section: Receptor-binding Agents (Receptor Hot Spots)mentioning
confidence: 92%
“…(53,54) Briefly, PC12 cells or nnr5-TrkC cells were plated at low density in complete media and allowed to adhere to the dish. Then the indicated treatment (NGF, NT-3 or peptidomimetics) was added for 48-72 h. The morphology of the cells was scored from pictures taken randomly and in a blinded fashion (4 pictures/well, 4 independent wells per condition).…”
Section: Methodsmentioning
confidence: 99%